Reconfiguration, restructuring and firm performance: Dynamic capabilities and environmental dynamism - Girod, Stéphane J. G.; Whittington, Richard (Strategic Management Journal, 2017)
Research summary: Reorganization has been proposed as a key dynamic capability. This study compares the performance outcomes of two forms of reorganization, differing in their pervasiveness: organizational restructuring and organizational reconfiguration. Our dynamic panel data analysis of large U.S. corporations between 1985 and 2004 finds contrasting performance outcomes for these two forms of reorganization: in general, the more pervasive restructuring is associated with positive performance outcomes, while the more limited reconfiguration is associated with negative performance outcomes. However, outcomes vary by environment. Consistent with dynamic capabilities theory, we find evidence that in dynamic environments reconfiguration outcomes turn positive, while restructuring outcomes turn negative. We discuss implications for dynamic capabilities theory and managerial policy . Managerial summary: Firms need to reorganize in order to adapt to change. This study compares the financial performance consequences of two forms of reorganization: organizational restructurings and organizational reconfigurations. Restructurings involve fundamental change in organizational principles and are typically irregular; reconfigurations involve incremental change and are frequent. Examining a set of large U.S. corporations, we find these two forms of reorganization have contrasting financial consequences, depending on context. In the general case, fundamental restructurings have positive consequences, while incremental reconfigurations have negative consequences. However, this general result reverses in specifically dynamic environments, where reconfigurations are positive financially, while restructurings are negative. We conclude that the relative frequency of reconfigurations helps adaptation in dynamic environments. Managers should choose forms of reorganization according to the rate of environmental change . Copyright © 2016 John Wiley & Sons, Ltd.